2017
DOI: 10.18632/oncotarget.16303
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fli-1 in astrocytoma is associated with poor prognosis

Abstract: BackgroundAstrocytoma, a common and highly malignant type of brain tumor, is associated with poor overall survival despite advances in surgical treatment, radiotherapy, and chemotherapy. The nuclear transcription factor Fli-1 has been shown to increase cellular proliferation and tumorigenesis in many types of cancer; however, previous reports have not described a correlation between clinical outcomes and Fli-1 in astrocytoma patients. The present study aimed to elucidate the clinical role of Fli-1 in astrocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…Aberrant expression of FLI1 is associated with hematological malignancies and solid tumors [6163]. Altered expression of FLI1 is also linked with tumor aggressiveness [63] and poor prognosis [64]. In our study, we have observed higher levels of FLI1 expression with the concomitant upregulation of CCL5 and the increased number of macrophages in human AIP pos tumors, supporting a crucial role for FLI1 and CCL5 in macrophage recruitment.…”
Section: Discussionsupporting
confidence: 75%
“…Aberrant expression of FLI1 is associated with hematological malignancies and solid tumors [6163]. Altered expression of FLI1 is also linked with tumor aggressiveness [63] and poor prognosis [64]. In our study, we have observed higher levels of FLI1 expression with the concomitant upregulation of CCL5 and the increased number of macrophages in human AIP pos tumors, supporting a crucial role for FLI1 and CCL5 in macrophage recruitment.…”
Section: Discussionsupporting
confidence: 75%
“…A reduction of FLI1 expression resulted in a reduction of h TERT , CCND1 and E2F2 transcript levels and less proliferation. Similar observations had already been made for CCND1 in astrocytoma . Strikingly, however, FLI1 knockdown in a normal lung cell line led to rapid progression through the cell cycle.…”
Section: Discussionsupporting
confidence: 84%
“…As a member of the ETS transcription factor family, FLI1 was known to regulate the expression of oncogenes, tumour suppressor genes, and some genes involved in maintaining vascular homoeostasis such as VE-cadherin, platelet endothelial cell adhesion molecule 1. 26,28,45 In GECs, we found that FLI1 was highly expressed and knockdown of FLI1 downregulated claudin-5, occludin and ZO-1 expression, which increased BTB permeability. Similarly, knockdown of FLI1 and ETS-related gene, its closest homolog, increased human pulmonary endothelial cell monolayer permeability with capacity like that of vascular endothelial growth factor.…”
Section: Combined Treatment Of Circ-usp1 and Mir-194-5p Promoted Domentioning
confidence: 87%
“…23 In human tissues, FLI1 is abnormally expressed in some solid tumours, including Ewing sarcoma, breast cancer and astrocytoma. [24][25][26] In endothelial cells, FLI1 is a regulator of vessel maturation and stabilization via modulating expressions of genes involved in maintaining vascular homoeostasis and integrity. 27,28 However, a little attention has been directed to clarify the possible role of FLI1 in GECs and BTB permeability.…”
mentioning
confidence: 99%